A STUDY ON THE DETERMINATION OF RISK FACTORS ASSOCIATED WITH BABESIOSIS AND PREVALENCE OF BABESIA SP., BY PCR AMPLIFICATION, IN SMALL RUMINANTS FROM SOUTHERN PUNJAB (PAKISTAN) - Iqbal, F.; Fatima, M.; Shahnawaz, S.; Naeem, M.; Shaikh, R. S.; Ali, M.; Ali, M. (Edp Sciences S A, 2011)
Babesiosis is a parasitic infection due to the multiplication of tick borne parasite, Babesia sp., in erythrocytes of host, which includes a wide variety of vertebrates including small ruminants causing decreased livestock output and hence economic losses. The objective of the present study was to establish a PCR based method for the detection of Babesia sp. in small ruminant population in Southern Punjab and to determine the risk factors involve in the spread of babesiosis. A total of 107 blood samples were collected from 40 sheep and 67 goats in seven districts of Southern Punjab from randomly selected herds. Data on the characteristics of the animals and the herd were collected through questionnaires. 36 blood samples (34 % of total) produced the DNA fragment specific for 185 rRNA gene of Babesia sp., by PCR amplification, of which 20 were sheep and 16 were goats. Samples from all seven district contained Babesia positive samples and prevalence varied between 18 to 68 A). It was observed that male animals (P = 0.009) and young animals under one year of age (P = 0.01) were more prone to the parasite. It was observed that herds consist of more than 15 animals (P = 0.007), composed of mixed species of small ruminants (P = 0.022), associated with dogs (P = 0.003) and dogs having ticks on their bodies (P = 0.011) were among the major risk factors for the spread of babesiosis in small ruminants.
Keywords: sheep; goats; PCR amplification; Babesia sp.